Genome-wide association study of biological nitrogen fixation traits in mini-core cowpea germplasm - Gelase Nkurunziza; Emmanuel K. Mbeyagala; Emmanuel Amponsah Adjei; Isaac Onziga Dramadri; Richard Edema; Arfang Badji; Rahiel Hagos Abrah; Astere Bararyenya; Kpedetin Ariel Frejus Sodedji; Phinehas Tukamuhabwa; Mildred Ochwo Ssemakula; John Baptist Tumuhairwe; et al. (PLoS ONE, 2025)
Biological Nitrogen Fixation (BNF) efficiency in legume crops such as cowpea (Vigna unguiculata L. Walp) has been less documented yet is key in improving yield performance and restoring soil fertility in sub-Saharan Africa. Nevertheless, little progress has been made in understanding the gene control of the BNF traits in cowpea to sustain the development of smart agriculture in this part of the world. This study aimed to identify cowpea genotypes and map genomic regions for BNF traits for developing high nitrogen-fixing cultivars. A total of 241 mini-core cowpea genotypes were inoculated with Bradyrhizobium spp in a screen house for two cycles. Phenotypic data collected on the number of nodules (NN) per plant, nodule efficiency (NE) in percentage, and nodule dry weight (NDW) per plant revealed significant differences implying high genetic variability in the mini-core population for nodulation capacity. Fifteen significant association signals were identified for BNF traits on nine chromosomes except Vu02 and Vu09 when two multi-locus models were considered. Markers accounting for over 15% variation for BNF traits included 2_31410 (2.32Mb) on Vu05 and 2_45545 (24.93Mb) on Vu06 for NN, 2_06530 (56.64Mb) and 2_27028 (34.31Mb) on Vu01 for NE and 2_50837 (10.07Mb) on Vu01 and 2_11699 (34.41Mb) on Vu07 for NDW, respectively. Additionally, positional candidate genes near the peak markers that encode genes associated with BNF in cowpea included Vigun06g121800, Vigun01g160600, Vigun10g014400, Vigun07g221500, Vigun07g221300 and Vigun11g096700. The genotype TVu-1477 was identified to have favorable alleles for both three studied traits. The significant markers identified in this study can be converted to Kompetitive Allele Specific-PCR (KASP) markers to accelerate the development of high-yielding cowpea varieties that also enhance soil fertility.